Developing MSMEs through Hongkong Caterpillar Cultivation - Tanjung, Abdillah Rizki; Misrah; Nisa Syahrani; Nurul Fitriyani; T. Lailan Safinah (Jurnal Dinamika Sosial Ekonomi, 2025)
This study analyzes the development strategy of Hong Kong caterpillar cultivation MSMEs (Tenebrio molitor) in Suka Makmur Village, Lalat Regency. With a qualitative approach of case studies on 10 selected respondents, data was collected through interviews, observations, and documentation, and then analyzed thematically. The results showed an average production of 65–75 kg per cycle with an initial capital of IDR 1,500,000. The running nucleus-plasma partnership pattern is asym-metrical, limiting market access and profit margins for farmers, although local innovations in feed and reinvestment support business sustainability. The main obstacles include limited capital, dependence on one core partner, and low digital marketing competence. On the other hand, these efforts contribute to increasing income, job creation, and converting organic waste into fertilizer. As a recommendation, the development strategy is focused on increasing human resource capacity, product diversification, digital marketing, and expanding access to financing and market networks to support the independence and competitiveness of MSMEs.